WORK SATISFACTION VALUE VIEWED FROM REACTION OF TRANSFORMATIONAL LEADERSHIP, PERFORMANCE ASSESSMENT AND TRAINING VARIABLES - Peri Sandria, Aji; Irfan Noviandy Aulia (Dinasti International Journal of Management Science, 2020)
This research was done because wants to explore regarding those influence which come from transformational leadership, performance assessment and training against work satisfaction at PT Pelat Timah NusantaraTbk in Cilegon. This research has include in qualitative research by causality design to prove those causal relationship between several variables such as transformational leadership (X1), performance assessment (X2), training (X3) and work satisfaction (Y). samples used which amounted to 99 people with sampling technique used non probality sampling and sample selected was done by random sampling. Scores of statements on questionnaire used a Likert scale of 1-5. Data analysis used SEM (Structural Equation Modeling) or Structural Equation Model whereas data processed by Partial Least Square (Smart-PLS) version 3.0. These results from research could be defined as follows: transformational leadership has mutual reaction to work satisfaction, performance assessment has beneficial impact over work satisfaction, training has positive influence towards work satisfaction and transformational leadership, performance assessment and training simultaneously influence on work satisfaction at PT Pelat Timah NusantaraTbk in Cilegon.